Experimental and Numerical Studies on the Mechanical Behavior of a Novel Bidirectional, Prestressed, Prefabricated, Composite Hollow-Core Slab - Junyan Jin; Weicheng Hu; Fuyan Zheng; Bitao Wu (Buildings)
Prestressed, precast composite panels are a type of building component that combines prestressing technology with composite materials; but, for most of them, it is difficult to balance structural stress performance and assembly efficiency. This paper proposes a series of novel bidirectional, prestressed, prefabricated, composite slabs, aiming to enhance their bidirectional force characteristics and assembly efficiency. By implanting a kind of specially designed concrete movable core rib with the same geometry as the cavity in the hollow-core slab at medium spacing, the transverse stressing performance of the structure is enhanced without affecting the unidirectional structural performance. Then, in the pre-set transverse apertures, several pieces of unidirectional, prestressed, precast hollow-core slabs that are implanted in the core mold are connected in series with high-strength strands and prestressed; finally, we obtain a bidirectional, prestressed, prefabricated composite slab. Two types of slabs (i.e., 3.3 m × 4.5 m and 4.5 m × 4.5 m) are selected and their mechanical behavior is investigated experimentally and by the finite element method, and the results are in good agreement. The proposed bidirectional, prestressed, precast composite slab not only has better overall bearing performance but also improves the structural stiffness and assembly rate, which can greatly improve the economic benefits and is of great significance for the popularization and application of assembled concrete structures.